Frequency of aspirin use in patients with type 2 diabetes: Is there any effect of concomitant diseases? (Annals of Medical Research, 2021)
Aim: Current guidelines recommend the use of low-dose aspirin in diabetic patients with increased cardiovascular disease risk with no risk of bleeding to prevent cardiovascular events. The aim of this study was to investigate the frequency of aspirin use in Type 2 Diabetes Mellitus and the effects of concomitant diseases.Material and Methods: Our retrospective and cross-sectional study was planned of data for rate of aspirin use in Type 2 Diabetes mellitus patients. In our study, the socio - demographic characteristics of the participants, their concomitant diseases with Type 2 DM and the drugs they used were questioned. Chi-square test was used for the analysis of categorical variables. P0.05 was considered statistically significant.Results: The mean age of the 910 participants was 57.27±10,00. 64.2% of the participants were female and 35.8% were male. Hypertension was the most common concomitant disease in type 2 DM. The prevalence of aspirin use was found to be %38.6. There is a statistically significant difference between aspirin use rates according to genders (p 0.05). Aspirin use was significantly higher in those who quit smoking and those with concomitant disease with type 2 DM. (p0.05). Conclusion: The rate of aspirin use in our diabetic group was insufficient. In order to increase the use and awareness of aspirin, the factors affecting the use of aspirin should be investigated.
Keywords: Aspirin; type 2 diabetes mellitus; risk factors; cardiovascular disease